2019
DOI: 10.1039/c9ra06547d
|View full text |Cite
|
Sign up to set email alerts
|

High pressure extraction of bioactive diterpenes from the macroalgae Bifurcaria bifurcata: an efficient and environmentally friendly approach

Abstract: Bioactive linear diterpenes were selectively extracted from the macroalga Bifurcaria bifurcata through optimized high-pressure extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
2
1
Order By: Relevance
“…The lowest values (0.11 and 7.50 mg/ml respectively) was recorded for B. bifurcata, which indicated that the latter might more easily reach therapeutic concentration in further biological studies. These values were below that reported earlier by Pais and al. (2019), where extraction was performed from the same seaweed using dichloromethane solvent.…”
Section: Determination Of Mic and Mbccontrasting
confidence: 80%
“…The lowest values (0.11 and 7.50 mg/ml respectively) was recorded for B. bifurcata, which indicated that the latter might more easily reach therapeutic concentration in further biological studies. These values were below that reported earlier by Pais and al. (2019), where extraction was performed from the same seaweed using dichloromethane solvent.…”
Section: Determination Of Mic and Mbccontrasting
confidence: 80%
“…The antioxidant activity against DPPH of Pinus spp. bark extracts was approached as explained before [21,30] and adapted to the 96-well plate scale. Ascorbic acid was used as the antioxidant reference, being dissolved in methanol/water (50:50, v/v) at 1 mg mL −1 .…”
Section: Dpph Free Radical Scavenging Effectmentioning
confidence: 99%
“…HPE induces a significant pressure gradient between the cell's interior and exterior, inducing the structural deformation of the cell walls and membranes. This deformation increases the cells' permeability and, consequently, increases bioactive compound extraction into the solvent [18,19].…”
Section: Introductionmentioning
confidence: 99%